A roadmap to implementing outpatient administration of bispecific antibodies in multiple myeloma - Garfall, Alfred L.; Banerjee, Rahul; Frenzel, Laurent; Khandanpour, Cyrus; Lin, Yi; Ottoni, Erica; Rifkin, Robert; Rockwell, Sarah; Rodriguez, Cesar; Villefort, Humberto; Zamagni, Elena (Frontiers in Oncology, 2025)
IntroductionBispecific antibodies (BsAbs) are novel immunotherapy agents for the treatment of relapsed/refractory multiple myeloma (RRMM). Currently, 3 BsAbs (teclistamab, talquetamab, and elranatamab) are approved for the treatment of RRMM. Administering BsAbs in different practice settings is crucial to improving treatment access and patient outcomes. This report provides actionable guidance to implement safe and effective administration of BsAbs for patients with RRMM in outpatient and community settings.MethodsThree clinician advisory workshops were held in the United States, Europe, and Latin America to discuss key factors to operationalize BsAb use in outpatient and community settings, focusing on the critical phases of practice setup, treatment initiation, and ongoing management.ResultsBsAb administration in outpatient and community settings requires careful planning, a well-prepared multidisciplinary team (MDT) of healthcare professionals, and clear protocols, including MDT composition, roles/responsibilities, capacity planning, patient selection criteria, step-up dosing procedure, admission processes, patient/caregiver education requirements, and adverse event (AE) monitoring/management. Comprehensive MDT training on protocols and preparedness to manage AEs is essential. Patients initiating outpatient BsAb therapy should have a reliable caregiver, access to a hospital, controlled comorbidities, and no active infections. Ensuring patients and caregivers understand the benefits, risks, and expectations of BsAb therapy is vital for successful treatment and a positive patient experience.ConclusionAdministering BsAbs in outpatient and community settings can be done safely and effectively with appropriate planning and protocols. Enabling safe and effective BsAb administration in these settings is essential to ensure more patients with RRMM have access to treatment and improved outcomes.